Transanal endoscopic microsurgical submucosal dissection (TEM-ESD) for rectal adenomas: a retrospective cohort study of 145 consecutive cases - Kouladouros, Konstantinos; Baral, Jörg (Langenbeck's archives of surgery, 2022)
Transanal endoscopic microsurgery (TEM) and endoscopic submucosal dissection (ESD) are currently the two most popular methods for resecting large rectal adenomas en bloc. However, damage to the mesorectum in the case of TEM, plus the technical challenges and long procedure times of flexible ESD, are major disadvantages of these procedures. Transanal endoscopic microsurgical submucosal dissection (TEM-ESD) is a new technique, combining the ergonomic features of TEM with the minimally invasive approach of ESD. The aim of our study was to assess the feasibility and safety of TEM-ESD for resection of large rectal adenomas.
Gesehen am 26.09.2023